2020
DOI: 10.1161/strokeaha.120.029279
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Goal-Directed Therapy on Delayed Ischemia After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose: Delayed cerebral ischemia (DCI) is the most important cause for a poor clinical outcome after a subarachnoid hemorrhage. The aim of this study was to assess whether goal-directed hemodynamic therapy (GDHT), as compared to standard clinical care, reduces the rate of DCI after subarachnoid hemorrhage. Methods: We conducted a prospective randomized controlled trial. Patients >18 years of age with an aneurysmal subarachnoid hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…Given that optimized targets for the administration of hemodynamic augmentation methods have not been well-defined, GDHT aims to address this issue by applying advanced hemodynamic monitoring to guide volume therapy. The results from a prospective RCT investigating the risk reducing effects of a GDHT protocol for DCI were reported by Anetsberger et al [93]. This study of 108 patients randomly assigned to GDHT or standard therapy found that the GDHT group had significantly lower odds of DCI (odds ratio: 0.324; 95% CI 0.11-0.86; p = 0.021), and a significantly greater proportion of patients achieving good outcome at 3 months, as measured by a GOS score of 5.…”
Section: Preventionmentioning
confidence: 82%
“…Given that optimized targets for the administration of hemodynamic augmentation methods have not been well-defined, GDHT aims to address this issue by applying advanced hemodynamic monitoring to guide volume therapy. The results from a prospective RCT investigating the risk reducing effects of a GDHT protocol for DCI were reported by Anetsberger et al [93]. This study of 108 patients randomly assigned to GDHT or standard therapy found that the GDHT group had significantly lower odds of DCI (odds ratio: 0.324; 95% CI 0.11-0.86; p = 0.021), and a significantly greater proportion of patients achieving good outcome at 3 months, as measured by a GOS score of 5.…”
Section: Preventionmentioning
confidence: 82%
“…Patients were enrolled between March 2013 and December 2015 9 . Both, outcome and troponin t data, were available in 106 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Troponin T measurements were obtained prospectively in the frame of a randomized, controlled clinical trial exploring the association of goal-directed hemodynamic therapy and outcomes after SAH at a University Hospital in Germany (Klinikum rechts der Isar, Technical University Munich) 9 . The study was approved by the local ethics committee (Ethics Commission of the Medical faculty, Technical University of Munich, ID: 5425-12) and was first registered at 16/04/2013 at clinicaltrials.gov; Identifier: NCT01832389.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This single-center randomized controlled prospective study was conducted to test the theory that goal-directed hemodynamic therapy (GDHT) would reduce DCI after SAH. 19 One hundred and eight patients with similar characteristics (55% coiling, 45% clipping) were randomized to two groups-GDHT group and the control group. Both the groups had similar ICU care.…”
Section: Impact Of Goal-directed Therapy On Delayed Ischemia After Aneurysmal Subarachnoid Hemorrhage 19mentioning
confidence: 99%